Neoliberal burdens for women in academy: 'how dare we not work'/Akademideki kadinlarin neoliberal sikintilari: 'olur mu hic calismamak' - Simsek, Burcu (2016)
In this article, I discuss the potential of digital storytelling as a site where feminist scholars in academia can get together to reflect upon their concerns about neoliberal burdens in academia. I rely on the recent literature about the feminist interventions in higher education in addition to giving an account of the grass-roots digital storytelling movement around the world and its feminism oriented journey in Turkey. Focusing on the digital stories told at the pre-conference digital storytelling workshop in EMU (Eastern Mediterranean University) immediately before the 5th International Conference on Gender Studies in March 2015, the aim of that digital storytelling workshop was not only to facilitate the creation of digital stories told by feminist academics but also to carry these digital stories into the program of the conference in a special session that hosted both the screening of these digital stories and an open discussion about our neoliberal concerns in academia and everyday life. This article also provides an account of the main discussions and attempts to suggest the digital storytelling workshop as a tool for broadening the interactions between academic and activist feminisms.